Die plek en funksle van bestuur in die kerk - Berg, A. A. van den (Koers, 1999)
The place and function of management in the churchIn this article attention is given to general management as a solution to the current management problem in congregations. Management as a science is not unfamiliar in the church, but it has merely been neglected. The meaning of the term “church" as used in both the Old Testament and the New Testament is examined. Management within the church will have to uphold the nature, being, character, purpose and structure of the congregation according to the Word of God. Management will have to be a process by which believers continuously engage in congregational activities, try to use human and other resources as efficiently as possible, in order to fulfil all the ministry needs o f the congregation and to achieve specific goals. To be able to achieve this, the basic management tasks of planning, organising, activating and controlling have to be undertaken. The church should apply management principles to enable the church to become what it should be according to the will/intention of God.